Overweight in childhood cancer survivors: the Swiss Childhood Cancer Survivor Study. Issue 1 (26th January 2018) - Belle, Fabiën N; Weiss, Annette; Schindler, Matthias; Goutaki, Myrofora; Bochud, Murielle; Zimmermann, Karin; von der Weid, Nicolas; Ammann, Roland A; Kuehni, Claudia E
ABSTRACT: Background: An increased risk of becoming overweight has been reported for childhood cancer survivors (CCSs), in particular leukemia survivors, although the evidence is inconclusive. Objective: We assessed the prevalence of overweight in CCSs, with a focus on leukemia survivors, compared it with their peers, and determined potential risk factors. Design: As part of the Swiss Childhood Cancer Survivor Study, we sent a questionnaire between 2007 and 2013 to all Swiss resident CCSs aged <21 y at diagnosis who had survived ≥5 y. We calculated body mass index (BMI) from medical records at diagnosis and self-reported heights and weights at survey. We calculated BMI z scores by using Swiss references for children and compared overweight prevalence in CCSs, their siblings, and the general population with the use of the Swiss Health Survey (SHS) and assessed risk factors for being overweight by using multivariable logistic regression. Results: The study included 2365 CCSs, 819 siblings, and 9591 SHS participants. At survey, at an average of 15 y after diagnosis, the prevalence of overweight in CCSs overall (26%) and in leukemia survivors (26%) was similar to that in siblings (22%) and the general population (25%). Risk factors for being overweight in CCSs were male sex (OR: 1.8; 95% CI: 1.5, 2.1), both young (OR for ages 5–14 y: 1.6; 95% CI: 1.2, 2.3) and older (range—OR for ages 25–29 y: 1.7; 95% CI: 1.2, 2.4; OR for ages 40–45 y: 4.0; 95% CI: 2.5, 6.5) age at study, lower education (OR: 1.4; 95% CI: 1.1, 1.8), migration background (OR: 1.3; 95% CI: 1.1, 1.7), and no sports participation (OR: 1.4; 95% CI: 1.1, 1.7). Risk factors for overweight were similar in peers. CCSs treated with cranial radiotherapy (≥20 Gy) were more likely to be overweight than their peers (OR: 1.6; 95% CI: 1.2, 2.2). Conclusions: The prevalence of and risk factors for being overweight are similar in long-term CCSs and their peers. This suggests that prevention methods can be the same as in the general population. An important exception is CCSs treated with cranial radiotherapy ≥20 Gy who may need extra attention during follow-up care. This study was registered at clinicaltrials.gov as NCT03297034.